Breves consideraciones semánticas de género en torno al léxico «amoroso», a la retórica «erótica» y a las paremias misóginas - Martínez Garrido, Elisa (Cuadernos de Filología Italiana, 2006)
This article is based on the cognitive semantic study of the «courtesy» lexicon, on the «erotic» rethoric and the misogynist proverbs which defend the violence against women. With the study of erotic and sexual metaphores we have tried to show the deep androcentric and patriarchal substratum of our «amorous » rethoric, which always hides a sadistic and violent vision of the sexuality.